2023
DOI: 10.3390/ijms24010826
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Analysis of the Mads-Box Transcription Factor Family in Solanum melongena

Abstract: The MADS-box transcription factors are known to be involved in several aspects of plant growth and development, especially in floral organ specification. However, little is known in eggplant. Here, 120 eggplant MADS-box genes were identified and categorized into type II (MIKCC and MIKC*) and type I (Mα, Mβ, and Mγ) subfamilies based on phylogenetic relationships. The exon number in type II SmMADS-box genes was greater than that in type I SmMADS-box genes, and the K-box domain was unique to type II MADS-box TFs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 61 publications
(57 reference statements)
0
3
0
Order By: Relevance
“…The MADS-box genes are ubiquitous in plants, and they play crucial roles in various processes, including plant growth and development, stress response, signal transduction, and other processes. With the publication of high-quality genomes, numerous MADSdomain proteins have been extensively identified and characterized through comprehensive genome-wide identification and analysis of expression profiles, such as Arabidopsis (107 genes) [4], rice (75 genes) [65], tomato (131 genes) [66], potato (153 genes) [67], bread wheat (300 genes) [68], cucumber (43 genes) [69], Brassica rapa (167 genes) [70], radish (144 genes) [71], sesame (57 genes) [72], watermelon (39 genes) [73], moso bamboo (42 genes) [74], sorghum (65 genes) [75], apple (146 genes) [76], chrysanthemum (108 genes) [77], eggplant (Solanum melongena) (120 genes) [78], blueberry (249 genes) [79], chayote (Sechium edule) (70 genes) [80], poplar (105 genes) [81], pear (95 genes) [82], banana (96 genes) [83], grape (58 genes) [84], soybean (106 genes) [85], honeysuckle (Lonicera japonica) (48 genes) [86], Zea mays (211 genes) [87], and Rhododendron ovatum (77 genes) [88].…”
Section: Discussionmentioning
confidence: 99%
“…The MADS-box genes are ubiquitous in plants, and they play crucial roles in various processes, including plant growth and development, stress response, signal transduction, and other processes. With the publication of high-quality genomes, numerous MADSdomain proteins have been extensively identified and characterized through comprehensive genome-wide identification and analysis of expression profiles, such as Arabidopsis (107 genes) [4], rice (75 genes) [65], tomato (131 genes) [66], potato (153 genes) [67], bread wheat (300 genes) [68], cucumber (43 genes) [69], Brassica rapa (167 genes) [70], radish (144 genes) [71], sesame (57 genes) [72], watermelon (39 genes) [73], moso bamboo (42 genes) [74], sorghum (65 genes) [75], apple (146 genes) [76], chrysanthemum (108 genes) [77], eggplant (Solanum melongena) (120 genes) [78], blueberry (249 genes) [79], chayote (Sechium edule) (70 genes) [80], poplar (105 genes) [81], pear (95 genes) [82], banana (96 genes) [83], grape (58 genes) [84], soybean (106 genes) [85], honeysuckle (Lonicera japonica) (48 genes) [86], Zea mays (211 genes) [87], and Rhododendron ovatum (77 genes) [88].…”
Section: Discussionmentioning
confidence: 99%
“…This interaction is associated with increased expression of the biosynthetic genes CHS and DFR . In a comprehensive analysis of MADS-box genes in eggplant, Chen et al [ 83 ] identified six genes that are likely to be involved in anthocyanin biosynthesis due to their predicted MYB-binding sites and the correlation of their expression patterns with SmMYB113 expression, as well as biosynthetic pathway and other transcription factor genes ( SmWRKY44 ).…”
Section: Eggplantmentioning
confidence: 99%
“…Peach MYB10.1 is overexpression in tobacco plants causes changes in anther filament and pistil length, and developmental defects in male and female gametophytes by repressing NtMYB305 during flower development ( Rahim et al., 2019 ). The SlbHLH22 gene can promote the early flowering of tomatoes ( Waseem et al., 2019 ), whereas SmbHLH13 delays flowering by downregulating key flowering genes ( Chen et al., 2023 ). FcbHLHs are specifically expressed in female flower tissues ( Song et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%